The Fractured Model Study of Low-Permeability Reservoir in Xinli Oil Field - Xue, Yongchao; Wang, Longjun; Zhao, Xiaoliang; Tian, Hua (Frontiers in Earth Science, 2022)
With the development of the petroleum industry, the importance of low permeability reservoirs becomes clear. The fracture, which serves as the notable characteristic of a low permeability reservoir, controls the flow system of reservoir fluid, restrain the development effect. Finding ways to recognize the fracture by using the normal data and build the fracture 3D model are the important and difficult points of low permeability development, according to this problem, the author carries on a helpful probe. Firstly, from similar outcrop and drilling core study the fractured original model, build the knowledge base of fracture. Secondly, based on analysis of the principle of dual-later log identification fracture, the core calibration was used to make logging, Using dual-later log recognize the fracture in wells. Thirdly, based on analysis the principle of the fractal kriging method and the inter-well fractures were predicted with the fractural kriging method. Finally, the 3-D model of fracture was built with fractural-random simulation. The result is the 3-D model in accord with the fact of the development. So the method is correct.